Smart metering design and applications - Weranga, K.S.K; Kumarawadu, Sisil; Chandima, D. P. (SpringerBriefs in Applied Sciences and Technology, 2014)
Taking into account the present day trends and the requirements, this Brief focuses on smart metering of electricity for next generation energy efficiency and conservation. The contents include discussions on the smart metering concepts and existing technologies and systems as well as design and implementation of smart metering schemes together with detailed examples.